Do Thickening Agents Used in Dysphagia Diet Affect Drug Bioavailability? - EROĞLU ERDEM, ÇİĞDEM (My University, 2022)
Swallowing oral solid dosage forms is challenging in patients with dysphagia who are at risk of aspiration or choking. The most common method to facilitate drug administration in dysphagia patients is to mix the powdered drug with a small amount of thickened water, however little is known about the effects of this method on in vivo bioavailability of drugs. This study aimed to evaluate the impact of thickened liquids on dissolution rate and bioavailability of levetiracetam as a model drug. Powdered commercial tablets of levetiracetam, carbamazepine, atenolol and cefixime were mixed with water thickened with two commercial thickeners, modified maize starch (MS) and xanthan gam (XG), at three thickness levels: nectar, honey and pudding in test groups, and mixed with only water in the control group. At the first stage, the effects of thickened water on in vitro drug release of 4 drugs (levetiracetam, carbamazepine, atenolol and cefixime) were tested by using dialysis membrane method. Addition of both thickeners significantly reduced the release of three drugs compared to the control group, except carbamazepine. Levetiracetam which had the highest solubility was chosen as the model drug for in vivo experiments. In the second stage, New Zealand albino female rabbits (n=24) were divided into two groups as: control group (water+drug, n=6) and test group (thickened water+drug, n=18). Powdered levetiracetam tablets were mixed with water thickened with XG (n=9, 1.2%, 2.4%, 3.6%) and MS (n=9, 4%, 6%, 8%) at three thickness levels and administered to the rabbits by intragastric gavage. Blood samples were collected at 9 time points following administration. After two-weeks of wash-out, test groups were crossed over and sample collection was repeated. Blood samples were analysed using liquid chromatography with tandem mass spectrometry (LC-MS/MS). An in vitro-in vivo correlation (IVIVC) model was developed using in vitro drug dissolution (%) and in vivo plasma concentrations of levetiracetam for control group and test groups. The peak plasma concentration (C-max) was lower and time to reach C-max (t(max)) was relatively higher in test groups compared to control group. The lowest C-max was detected at the highest thickness level, however, the differences between groups were not statistically significant (p=0.117 and p=0.495 for C-max and t(max), respectively). No significant difference in total amount of levetiracetam absorbed (AUC) was found between groups (p=0.215 and p=0.183 for AUC(infinity) and AUC(last), respectively). The comparisons according to the type of thickener also revealed that pharmacokinetic parameters did not significantly differ between groups, except for a significantly lower C-max when drug was mixed with MS-thickened water at nectar consistency (1.2%) compared to drug mixed with XG (4%) at the same thickness level (p=0.038). A good correlation was observed between in vitro and in vivo data, which was characterized by higher r(2) values as the concentration of the thickening agents was increased, but not for all thickness levels studied, indicating an inability of this in vitro model to fully predict the in vivo response. These results suggest that regardless of the thickness level, the administration of levetiracetam with two commercial thickening agents commonly used in dysphagia for safe swallowing, do not affect the pharmacokinetic efficiency and thus, the bioavailability of the drug.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides; Dysphagia; Thickeners; Xanthan gum; Modified starch; Viscosity; In vitro drug release; Bioavailability; OROPHARYNGEAL DYSPHAGIA; GASTROINTESTINAL-TRACT; TABLET DISINTEGRATION; WATER DIFFUSIVITY; FORM MODIFICATION; EUROPEAN-SOCIETY; BOLUS VISCOSITY; OLDER-ADULTS; WHITE PAPER; FOOD